Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru SD di Kecamatan Lumut Kab. Tapanuli Tengah Tahun Pembelajaran 2023/2024 - Evi Vitriani Sianipar; Oktober Tua Aritonang; Eben Haezarni Telaumbanua (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The purpose of this research is 1) to determine whether or not there is an influence of school principal leadership on teacher performance in elementary schools in Lumut sub-district, regency. Central Tapanuli year of study 2023/2024; 2) to determine whether or not there is an influence of teacher work motivation on teacher performance in elementary schools in Lumut district, regency. Central Tapanuli year of study 2023/2024; 3) to determine the simultaneous influence of principal leadership and teacher work motivation on teacher performance in elementary schools in Lumut district, regency. Central Tapanuli year of study 2023/2024. The method used in this research is a quantitative research method. The population is all teachers at State Elementary School 157624 Lumut Nauli State Elementary School 158460 Sialogo, State Elementary School 158468 Lumut 5 and State Elementary School 158467 Lumut Maju, State Elementary School 153070 Lumut 1, State Elementary School 155687 Masundung located in Central Tapanuli Regency totaling 100 people and a sample of 40 people was taken using random sampling techniques. Data was collected using a closed questionnaire with 86 items. The results of data analysis show that: 1) the calculated F value > F table between the principal's leadership on teacher performance is 17.972 > 3.23, thus it is known that there is an influence between the principal's leadership on the performance of elementary school teachers in Lumut District, Kab. Middle Tapanuli for the 2023/2024 Academic Year, which is 32.1%, 2) the calculated F value > F table between work motivation and teacher performance is 14.510 > 3.23, thus it is known that there is an influence between work motivation and the performance of elementary school teachers in Lumut District Kab. Tapanuli Middle School Year 2023/2024 is 27.6%, 3) the calculated F value > F table between the principal's leadership and work motivation on teacher performance is 12.259 > 3.23, thus it is known that there is an influence between the principal's leadership and motivation work on the performance of elementary school teachers in Lumut District, Central Tapanuli Regency Middle School Year 2023/2024 is 39.9%, thus Ha is accepted and H0 is rejected.